2023
DOI: 10.1186/s12967-023-04003-y
|View full text |Cite
|
Sign up to set email alerts
|

Metabolically healthy obesity is associated with higher risk of both hyperfiltration and mildly reduced estimated glomerular filtration rate: the role of serum uric acid in a cross-sectional study

Abstract: Background The impact of metabolically healthy obesity (MHO) on kidney dysfunction remains debatable. Moreover, few studies have focused on the early stages of kidney dysfunction indicated by hyperfiltration and mildly reduced eGFR. Thus, we aimed to investigate the association between the MHO and early kidney dysfunction, which is represented by hyperfiltration and mildly reduced estimated glomerular filtration rate (eGFR), and to further explore whether serum uric acid affects this associatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…We conducted a cross-sectional study from December 2016 to December 2017. We recruited 1,328 permanent residents aged ≥ 40 years who had lived in the communities of Zhonglou District, Changzhou City, Jiangsu Province, China more than 6 months [ 23 , 24 ]. We excluded those with missing information on Lp(a), creatinine, and serum cystatin C (Scys) and eGFR < 60 mL/min/1.73 m 2 and deleted extreme values of Lp(a).…”
Section: Methodsmentioning
confidence: 99%
“…We conducted a cross-sectional study from December 2016 to December 2017. We recruited 1,328 permanent residents aged ≥ 40 years who had lived in the communities of Zhonglou District, Changzhou City, Jiangsu Province, China more than 6 months [ 23 , 24 ]. We excluded those with missing information on Lp(a), creatinine, and serum cystatin C (Scys) and eGFR < 60 mL/min/1.73 m 2 and deleted extreme values of Lp(a).…”
Section: Methodsmentioning
confidence: 99%
“…Zhang et al reported that subjects with metabolically healthy obesity presented both a significantly reduced and increased eGFR, and the association became not significant by adjusting for serum uric acid. 3 Serum uric acid would interact with kidney function, and a mediation analysis may be one of the effective methods to evaluate the causal association between eGFR and mortality. 4 Fang et al 1 analyzed data in patients with hypertension, and cardio-renal effect on mortality would be a key point for the analysis.…”
mentioning
confidence: 99%